Labor Productivity of Home Based and Outdoor Working Women in Pakistan: An Implications from Human and Social Capital - Rashid, Ayesha; Faridi, Muhammad Zahir (Pakistan Journal of Humanities and Social Sciences, 2023)
Women in Pakistan are significantly contributing to national economy but their work is undervalued and they are facing a seemingly invincible array of barriers which are preventing them to become more productive and empowered citizens. The current study aims to empirically analyze the impact of various determinants particularly human capital, social capital, awareness to labor laws and role of middleman on labor productivity of home based and outdoor women workers in Multan Division, Punjab, Pakistan using ordinary least square methodology. The results indicated that human as well as social capital has significant impact on the productivity of women. The coefficient of age, ownership of assets, family expenditures, self-employment, working as employee, worker’s satisfaction, awareness about labor laws, urban location, marital status and joint family setup have a positive, while age-squared, number of children, restrictions to achieve education have a negative impact on labor productivity of women both home based and outdoor. The results provide evidence to suggest that policy makers should focus on human as well as social capital to improve women’s capability to enrich their labor productivity, their living standards and growth of economy.